WAYS TO DEVELOP THE FINANCIAL MARKET INFRASTRUCTURE - Shodiyev Odiljon Salim O’g’li (American Journals, 2023)
This article discusses the theoretical basis for the development of financial market inflation in our country, as well as existing situations, analysis and prospective plans.
Keywords: financial market infrastructure, securities, capital, bonds, action strategy, financial instruments.